1. The problem statement, all variables and given/known data Let's say u(ct) = logct The first order conditions are: ct: βt/ct-λt = 0 (t = 0, 1, 2, ...) kt+1 = -λt + λt+1R = 0 (t = 0, 1, 2, ...) Delete λt and λt+1 (Euler equation) and you get 1/ct = βR/ct+1 ∴ct+1 = βRct 2. Relevant equations This was part of an explanation of a proof, and I am stuck on "Delete λt and λt+1 (Euler equation) and you get 1/ct = βR/ct+1" I am not sure how the two lamdas were deleted, nor the rule that was applied. 3. The attempt at a solution A search for "euler equation" has been unfruitful, mathematical manipulation yields: λt = βt/ct Any help would be greatly appreciated.